(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Mechanical ventilation (MV) is a life-saving intervention in the intensive care unit that should be considered for patients with respiratory failure. Objective: The purpose of the present study was to compare the clinico-demographic characteristics and rapid shallow breathing index of patients on mechanical ventilation at intensive care unit. Methodology: This prospective cohort study was conducted in the Department of Anesthesia, Pain Palliative & Intensive Care Unit of Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2014 to December 2015 for a period of two (2) years. Patients on mechanical ventilation more than 48 hours with the age of 18 to 60 years after fulfilling the inclusion and exclusion criteria were included as study population. One type of ventilator (eVent Medical) was used in all patients. Primary and daily setting of ventilators and the decision to weaning of the patient was made by the ICU consultants. The rapid shallow breathing index (RSBI) was measured by the ratio of respiratory frequency (f) to average exhaled tidal volume (EVT). When rapid shallow breathing index was 105 breath/min/L or less and more than 105 breath/min/L were taken as low and high RSBI respectively. Result: A total number of 117 patients were recruited for this study after fulfilling the inclusion and exclusion criteria of which 92 patients were in low RSBI group and the rest 25 patients were in high RSBI group. The mean age was found 31.8±12.8 years in low RSBI group and 35.9±13.2 years in high RSBI group (p>0.05). It was observed that male was found 57(62.0%) in low RSBI group and 13(52.0%) in high RSBI group (p>0.05). It was observed that 14(15.2%) patients had laparotomy in low RSBI group and 4(16.0%) in high RSBI group (p>0.05). Surgical patients was found 27(29.3%) in low RSBI group and 11(44.0%) in high RSBI group (p>0.05). Conclusion: In conclusion there is no statistical significant relationship of age, gender and clinical diseases of the patients with low and high rapid shallow breathing index who are under mechanical ventilation at intensive care unit. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 92-96